Gaya Kepemimpinan dan Karekteristik Pemimpin yang Efektif - Husen Waedoloh; Hieronymus Purwanta; Suryo Ediyono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
Leaders have their own unique and distinctive traits, habits, temperament, character, and personality so that their behavior and style can be distinguished from others. This style or lifestyle will color his behavior and type of leadership. Leadership refers to someone influencing the behavior of others for a purpose. With power, leaders can influence the behavior of their subordinates. This study aimed to determine the characteristics of leaders and effective leadership styles. Ideal leadership is a dream or a hope for every organization. There are 8 (eight) ideal leadership characteristics, namely: honest, intelligent, responsible, visionary, correct, disciplined behavior, initiative and, direct. Character is the key to an organization's success. An organization will move forward or backward depending on the leader. Because the leader is the one who directs and determines the organizational objectives to be achieved. The method used in this research is the study of literature or library research and by conducting observational studies from previous studies. Library research, Researchers study and collect data through several kinds of literature and reading sources that support and are relevant to research. In this case, literature research is carried out through books, magazines, internet.